Male agility in relation to mating success in two non-territorial damselflies - de Almeida, Thais R.; Salomoni, Saul; Vilela, Diogo S. [UNESP]; Guillermo-Ferreira, Rhainer (Wiley, 2022)
Male body size is usually correlated with mating success in insects. For non-territorial species, the small male advantage hypothesis predicts that smaller males may be favoured in sexual selection because small body size may predict agility and manoeuvrability. Consequently, selection for male size may drive the evolution of female-biased sexual size dimorphism (SSD). Nevertheless, recent evidence shows that non-territorial male damselflies that actively search for females may be larger and more agile than those that perch and wait for females to appear. Thus, here we addressed whether the male size is an indicator of male agility and if it may be used to predict male reproductive success in two non-territorial damselflies. To this end, we conducted a field study with Acanthagrion truncatum Selys, 1876 and A. lancea Selys, 1876 (Zygoptera, Coenagrionidae). Males of A. truncatum adopt a sit-and-wait mating strategy, while the males actively search for females in A. lancea. Hence, we expected different selective forces acting on male body size and agility in these species. We compared the body size and wing length of mated and unmated males, and between sexes, to describe their patterns of SSD. Our results suggest that wing length can be used as a proxy for male body size and agility in both species. However, we have found no evidence for the small male advantage that could explain wing dimorphism in A. truncatum, nor selection for larger males in A. lancea. In conclusion, this study corroborates other studies that suggest agility cannot explain SSD in non-territorial damselflies and fail to support the small male advantage hypothesis.
Keywords: aerodynamics; allometry; Coenagrionidae; flight; reproductive behaviour; sexual selection